Food aid : its role in economic development - Organisation for Economic Co-operation and Development (Paris, Organisation for Economic Co-operation and Development., 1963)
This report investigates the possibilities for promoting economic development through programmes of food aid.
Includes bibliographical references: p. 83-85.
oif 26/02/2019
Loans
Keywords: Food relief; Surplus agricultural commodities; Economic assistance; Produce trade; Food supply; Developing countries